2002
DOI: 10.1067/mva.2002.118818
|View full text |Cite
|
Sign up to set email alerts
|

Technical details with the use of cryopreserved arterial allografts for aortic infection: Influence on early and midterm mortality

Abstract: In situ repair with cryopreserved arterial allografts achieves excellent early and late results in the treatment of aortic infection. However, distinct allograft-related technical problems had to be overcome to improve the outcome of patients with major vascular infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Cryopreservation has improved the permanence of allografts, but degeneration, possible aneurysmatic dilatation, and subsequent rupture remain challenging 22, 26, 27, 28. Also, availability and costs limit more widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation has improved the permanence of allografts, but degeneration, possible aneurysmatic dilatation, and subsequent rupture remain challenging 22, 26, 27, 28. Also, availability and costs limit more widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…In situ reconstruction with use of a prosthetic graft is attended by a greater risk of graft infection than extra-anatomical bypass procedure. Compared to synthetic grafts, the use of cryopreserved grafts has the advantage of low vulnerability to infection and limited immune response with better viability [28, 29]. This procedure is limited by its cost and the fact that it is not applicable in urgent situations because it needs to be ordered from an international graft banking center.…”
Section: Discussionmentioning
confidence: 99%
“…In their latest article Vogt et al [37]demonstrated that the viability of cryopreserved allografts preserved until after implantation could enhance the resistance to bacteria. In this regard, we think that the results of our study may contribute to improving surgical treatment for infectious diseases in the cardiovascular system, especially improving the repair of lesions in acute postoperative periods.…”
Section: Discussionmentioning
confidence: 99%